Contribution of inventor I.К. Matrosov to development of the brake system - S. S. Dovhaniuk (History of science and technology, 2013)
In the paper the Soviet scientists’ contribution to the development of brake gear, including freight trains air diffuser brake is analyzed. Particular attention is paid to the development of freight trains brakes of Matrosov system until 1959, which operating principle after improvements and enhancements remained in the basis work of the freight rolling stock air duct to the present day.